Study on Morphological Diversity of Some Tephrosia Species (Fabaceae) in Saudi Arabia - Al-Ghamdi, Faraj A. (Recent Research Advances in Biology Vol. 7, 2021)
Morphological characteristics of nine wild Tephrosia PERS species growing in Saudi Arabia were extensively studied in order to support diversity and simplify identification of these species. The macro and micro morphological features of the stem, leaves, flowers, and pods were studied. The most important characteristics used to make a distinction Saudi Arabia Tephrosia species were pod shape, colour, size, dehiscence and number of seeds per pod, inflorescence position, flower opening, shape of the upper 2 teeth of calyx, shape of sepals apex, shape of wings, length of hairs on ovary, direction of staminal tube tip, leaflets shape and surface, stem habit form and life spin. A key for the identification of the investigated species based on these morphological features is provided. Plant morphology has served largely for systematics, using morphological characteristics to carve up diversity into its systematic sub-units.